Successful treatment of kaposiform hemangioendothelioma with everolimus. Issue 3 (12th October 2014) - Uno, Teruaki; Ito, Shuichi; Nakazawa, Atsuko; Miyazaki, Osamu; Mori, Tetsuya; Terashima, Keita
<x xml:space="preserve">Abstract</x> There is currently no consensus on the second‐line management of Kaposiform hemangioendothelioma (KHE) that was resistant to prednisolone and vincristine. We described an eight‐year‐old male with KHE in the right femur that was resistant to prednisolone, vincristine and propranolol. Everolimus, an inhibitor of mammalian target of rapamycin (mTOR) at the dosage of 0.1 mg/kg/day, successfully decreased the tumor size and controlled the symptoms. Everolimus should be further studied as an alternative agent to sirolimus in the management of KHE. Pediatr Blood Cancer 2015;62:536–538. © 2014 Wiley Periodicals, Inc.